IMPLEMENTASI MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPAS KELAS IV - Rahma Rizky Sukma; Dina Prasetyowati; Mei Fita Asri Untari (STKIP Subang, 2023)
This study aims to improve science learning outcomes through the Problem Based Learning learning model. This type of research is Class Action Research where the research subject is class IV C of SD Negeri Rejosari 01, totaling 26 students. While the object in this study is the learning outcomes of the science content. The research data used is in the form of qualitative data and quantitative data. Based on the research results, it can be concluded that learning using the Problem Based Learning learning model can improve student learning outcomes. The learning outcomes in the pre-cycle showed that the level of mastery of learning outcomes was 15 students or 57.70% of the 26 students. In cycle 1 the level of mastery of student learning outcomes increased to 19 students or 73.07% of 26 students. Furthermore, in cycle II the level of mastery of student learning outcomes increased to 23 students or 88.46% of 26 students. This research was said to be successful because it had achieved a completeness indicator, namely ≥ 80% of the class average with KKM ≥ 70.